2016
DOI: 10.1093/ajh/hpw092
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Awareness, Treatment, and Control of Hypertension in the Southern Cone of Latin America

Abstract: This study indicates that the prevalence of hypertension is high while awareness, treatment, and control are low in the general population in the Southern Cone of Latin America. These data call for bold actions at regional and national levels to implement effective, practical, and sustainable intervention programs aimed to improve hypertension prevention, detection, and control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
3
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 27 publications
4
28
3
6
Order By: Relevance
“…Our study also showed that highly educated people usually had a lower rate of hypertension than those with low education levels. This finding was consistent with several other studies [23][24][25]. It may reflect that factors associated with hypertension are similar among different ethnicities.…”
Section: Discussionsupporting
confidence: 93%
“…Our study also showed that highly educated people usually had a lower rate of hypertension than those with low education levels. This finding was consistent with several other studies [23][24][25]. It may reflect that factors associated with hypertension are similar among different ethnicities.…”
Section: Discussionsupporting
confidence: 93%
“…Research on HTN prevalence, awareness, treatment, and control has been conducted in many regions of the world, with varying results. Prevalence of HTN has been reported to be as low as 13.4% in Bogota up to as high as 42.5% in several cities of Chile, Argentina, and Uruguay . In comparison, many other regions of the world have a prevalence that falls within this range, such as Canada (20%), China (29.6%), Korea (33.7%), Lebanon (36.9%), and Estonia (36%) .…”
Section: Introductionmentioning
confidence: 99%
“…Además, este trabajo muestra que, para ambos sexos, el riesgo de presentar HTA aumenta sobre los 25 años de edad, en personas con historia familiar de HTA y con diagnóstico de DMT2. Estos resultados coinciden con lo reportado por otros estudios que señalan que la edad se asocia independientemente con el desarrollo de HTA y que un bajo nivel de educación también influirá en su desarrollo 9,11,20 . A nivel antropométrico, el exceso de peso es, sin duda, uno de los principales factores de riesgo para el desarrollo de diferentes enfermedades crónicas no transmisibles.…”
Section: Discussionunclassified